Answer
Simplifying
9x + -7i = 3(3x + -7u)
Reorder the terms:
-7i + 9x = 3(3x + -7u)
Reorder the terms:
-7i + 9x = 3(-7u + 3x)
-7i + 9x = (-7u * 3 + 3x * 3)
-7i + 9x = (-21u + 9x)
Add '-9x' to each side of the equation.
-7i + 9x + -9x = -21u + 9x + -9x
Combine like terms: 9x + -9x = 0
-7i + 0 = -21u + 9x + -9x
-7i = -21u + 9x + -9x
Combine like terms: 9x + -9x = 0
-7i = -21u + 0
-7i = -21u
Solving
-7i = -21u
Solving for variable 'i'.
Move all terms containing i to the left, all other terms to the right.
Divide each side by '-7'.
i = 3u
Simplifying
i = 3u